2016
DOI: 10.1103/physrevd.93.062001
|View full text |Cite
|
Sign up to set email alerts
|

Neutron limit on the strongly-coupled chameleon field

Abstract: The physical origin of the dark energy that causes the accelerated expansion rate of the universe is one of the major open questions of cosmology. One set of theories postulates the existence of a self-interacting scalar field for dark energy coupling to matter. In the chameleon dark energy theory, this coupling induces a screening mechanism such that the field amplitude is nonzero in empty space but is greatly suppressed in regions of terrestrial matter density. However measurements performed under appropriat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…Matter wave interferometry is a powerful and extremely sensitive tool to probe effects ranging from material properties to foundational physics [1][2][3][4] . Although high sensitivity and accuracy are achieved due to matter waves' small deBroglie wavelength and statistical inference, these massive particles couple to external degrees of freedom (DOF) leading to loss of coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Matter wave interferometry is a powerful and extremely sensitive tool to probe effects ranging from material properties to foundational physics [1][2][3][4] . Although high sensitivity and accuracy are achieved due to matter waves' small deBroglie wavelength and statistical inference, these massive particles couple to external degrees of freedom (DOF) leading to loss of coherence.…”
Section: Introductionmentioning
confidence: 99%
“…Lemmel et al [162] recently presented phase shift measurements for neutron matter waves in vacuum and in low pressure helium using a method originally developed for neutron scattering lengths measurements. Li et al [163] reported an upper bound on the neutron-chameleon through the relative phase shift it would induce along one of the neutron paths inside a perfect crystal neutron interferometer. The amplitude of the chameleon field was actively modulated by varying the millibar pressures inside a dual-chamber aluminum cell.…”
Section: Limits On Hypothetical Gravity-like Interactionsmentioning
confidence: 99%
“…Amplitude division from Bragg diffraction off of crystal planes was later used to make perfect crystal NIs with Mach-Zehnder (MZ) path separations of several centimeters [4]. This relatively large path separation along with the macroscopic size of the interferometer contributed to its success in exploring the nature of the neutron and its interactions [5][6][7][8][9][10]. However, perfect crystal NIs possess a very narrow wavelength acceptance, are difficult to fabricate, and operate only under stringent forms of vibration isolation and beam collimation [11][12][13][14][15].…”
mentioning
confidence: 99%